PEDAGOGICAL AGREEMENTS OF FORMATION OF SCHOLARS' ESTHETU FEELINGS USING SYNTHESIS OF ARTS - I.V. Mohiley (Academy of Cognitive and Natural Sciences, 2022)
The article deals with detachment and substantiation of pedagogical agreements' maintenance according to the synthesis of arts for further perfection in the formation of scholars' esthetic feelings on art lessons.